To cognition of the scientific contribution of Professor L.I. Malyshev to the floristic research of Siberia and other territories: a brief analytical review - Doronkin Vladimir (EDP Sciences, 2021)
Analytical review of scientific contribution of Professor Malyshev is performed and presented on the floristic research of Siberia and other territories (Ural Mountains, Mongolia, Russian Far East, etc.). It was shown, that there were several stages in these researches: from Eastern Sayan to Stanovoy Uplands, Putorana Plateau, and then Central (Baikalian Siberia and Dahuria) Siberia, Siberia in whole, and joined flora of Siberia and Russian Far East, usung different methodical approaches (method of concrete flora of A.I. Tolmachev adopted to mountain regions, and various techniques of multivariate statistics, such as rank correlations for familiesspecies, families-genera, and genera-species in head parts of taxonomic spectra, usually consists of 10 to 20 taxa (families or genera). To solve some florogenetic issues, the concept of floristic complexes as stable groups of species located in a certain belt of mountains (for example, alpine and mountain-steppe) was proposed and applied. At all stages of floristic research, the task was set to maximally identify the species composition on territories of various sizes for subsequent subdivision, with the identification of the boundaries for floristic regions, subregions, provinces and sub-provinces. The local floras and working floristic districts were taken as the basic elements of such division.